Canada's Aboriginal Peoples and Health: The Perpetuation of Inequalities - Hornosty, J.; Gray, Dennis; Saggers, Sherry (Oxford University Press, 2012)
Who are Aboriginal Canadians and what is their reality? How is the health inequality experienced by Aboriginal Canadians being addressed? Why do such health inequalities persist today? Canada has a publicly funded health-care system that many Canadians understandably are proud of. However, not all peoples have benefited equally. The health status of Canada's original peoples on virtually all indicators of health is below that of non-Aboriginal Canadians. They have higher mortality and morbidity rates and higher incidences of tuberculosis, alcoholism, and suicide than the rest of the population. They also are more likely to be unemployed, to live in poverty and substandard housing, and to have lower education attainment levels. This chapter explores possible explanations for these equities and situates the existing inequality in a broader social and historical context Aboriginal people's experiences of colonization, dispossession, and marginalization from the dominant economy. As well, the chapter explores the health implications of these processes. Although efforts have been made to improve the health status of Aboriginal peoples, many structural inequalities remain.